Optimalisasi Literasi Bisnis Digital Pelaku UMKM Dalam Menyongsong Era Society 5.0 - Fadli Agus Triansyah; Sandi Jembar Wijaya; Erna Dwi Jayanti; Nurhuda Teapon; Rini Melani (CV. Ulil Albab Corp, 2023)
Era Society 5.0 is an era in which technology and humans coexist in order to improve the quality of human life on an ongoing basis. In this era, digital literacy is very important because humans must be able to master technology and information from digital devices effectively and efficiently. One sector that can benefit from digital literacy in the Society 5.0 era is MSMEs. The purpose of this service and training is to provide motivation to MSME actors who live around the Kec. Sukasari, Bandung City to increase digital literacy in the era of society 5.0 and carry out activities by providing activities and training such as presentation of material and questions and answers. Based on the several activities carried out, it is expected that some changes will occur, namely increasing the motivation of MSME actors in running their business, market identification, product/service differentiation, focus on quality, effective marketing, wise financial management, innovation and development and digitalization.